1991
DOI: 10.1016/0888-7543(91)90430-m
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the panhypopituitary dwarf mutation (df) on mouse chromosome 11 in an intersubspecific backross

Abstract: Ames dwarf (df) is an autosomal recessive mutation characterized by severe dwarfism and infertility. This mutation provides a mouse model for panhypopituitarism. The dwarf phenotype results from failure in the differentiation of the cells which produce growth hormone, prolactin, and thyroid stimulating hormone. Using the backcross (DF/B-df/df X CASA/Rk) X DF/B-df/df, we confirmed the assignment of df to mouse chromosome 11 and demonstrated recombination between df and the growth hormone gene. This backcross is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
3

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 49 publications
(13 reference statements)
1
36
0
3
Order By: Relevance
“…Although its precise function is not known, antibody neutralization of osteonectin in Xenopus embryos has been shown to disrupt caudal development in an analogous fashion to the backbone truncation and caudal defects observed in vt/vt embryos (Purcell et al 1993). Sparc had been mapped previously to the central portion of Chromosome 11 with a 99% probability of being within 3.9 cM of Csfgm (Buckwalter et al 1991). To evaluate Sparc as a candidate gene for vt, 173 backcross progeny were typed for Sparc using a restriction fragment-length protein (RFLP) revealed by Southern blot hybridization.…”
Section: Wnt-3a and Vt Cosegregate On Mouse Chromosome 11mentioning
confidence: 99%
See 1 more Smart Citation
“…Although its precise function is not known, antibody neutralization of osteonectin in Xenopus embryos has been shown to disrupt caudal development in an analogous fashion to the backbone truncation and caudal defects observed in vt/vt embryos (Purcell et al 1993). Sparc had been mapped previously to the central portion of Chromosome 11 with a 99% probability of being within 3.9 cM of Csfgm (Buckwalter et al 1991). To evaluate Sparc as a candidate gene for vt, 173 backcross progeny were typed for Sparc using a restriction fragment-length protein (RFLP) revealed by Southern blot hybridization.…”
Section: Wnt-3a and Vt Cosegregate On Mouse Chromosome 11mentioning
confidence: 99%
“…Probes were prepared by radiolabeling purified DNA fragments with [32p]dCTP (NEN) nucleotide by the random hexamer method (Feinberg and Vogelstein 1982). Hybridization of filters containing genomic DNA digested with BamHI with the SPARC probe detected a CASA/Rk-specific fragment of 3.1 kb (Buckwalter et al 1991) and a VT-specific fragment of 2.5 kb. The Wnt-3a eDNA probe detected an 8.8-kb CASA/Rk specific fragment and a 5.2'-kb VT-specific fragment in genomic DNA digested with BglI.…”
Section: Genetic Mappingmentioning
confidence: 99%
“…All other gene orders resulted in multiple double-crossover events. The genetic distance (cM) and standard error were calculated as previously described (Buckwalter et al 1991). The locations of the human genes are given in parentheses (Arbiser et al 1988;Ginns et al 1985;Nakai et al 1987;Seigel et al 1984).…”
mentioning
confidence: 99%
“…Pit-1 is required later for the continued expression of the Pit-1 gene itself and the proliferation and survival of these three cell types (Godfrey et al, 1993;Li et al, 1993;Rhodes et al, 1993). A mouse genetic defect, referred to as the Ames dwarf (df), was mapped to chromosome 11 (Bartke, 1965;Buckwalter et al, 1991) and proved to be cell-autonomous (Buckwalter et al, 1991), resulting in a hypoplastic anterior pituitary similar to that of the Snell and Jackson dwarfs. In contrast to the complete absence of somatotropes, lactotropes, and thyrotropes in the Snell mouse, the Ames mouse pituitary gland contains between Ϸ 1% (Gage et al, 1996b) and 0.001% (Andersen et al, 1995) of the normal complement of somatotropes as well as a few lactotropes and thyrotropes (Gage et al, 1996b).…”
mentioning
confidence: 99%
“…The region surrounding the df locus was generally mapped using a CAST/Ei ϱ C57BL/6J intercross and a Mus spretus ϱ C57BL/6J backcross to related CA-repeat markers (Dietrich et al, 1996) to the previously identified locations of the markers Pad-1 and the interleukin (IL) cluster (IL-3, IL-4, and IL-5) (Buckwalter et al, 1991). Four markers provided two proximal and two distal loci that were used to genotype progeny of a large intercross between Cast/Ei and DF/B df/df.…”
mentioning
confidence: 99%